Grey matter involvement by focal cervical spinal cord lesions is associated with progressive multiple sclerosis. (June 2016) - Kearney, Hugh; Miszkiel, Katherine A; Yiannakas, Marios C; Altmann, Daniel R; Ciccarelli, Olga; Miller, David H
Background: The in vivo relationship of spinal cord lesion features with clinical course and function in multiple sclerosis (MS) is poorly defined. Objective: The objective of this paper is to investigate the associations of spinal cord lesion features on MRI with MS subgroup and disability. Methods: We recruited 120 people: 25 clinically isolated syndrome, 35 relapsing–remitting (RR), 30 secondary progressive (SP), and 30 primary progressive (PP) MS. Disability was measured using the Expanded Disability Status Scale. We performed 3T axial cervical cord MRI, using 3D-fast-field-echo and phase-sensitive-inversion-recovery sequences. Both focal lesions and diffuse abnormalities were recorded. Focal lesions were classified according to the number of white matter (WM) columns involved and whether they extended to grey matter (GM). Results: The proportion of patients with focal lesions involving at least two WM columns and extending to GM was higher in SPMS than in RRMS ( p = 0.03) and PPMS ( p = 0.015). Diffuse abnormalities were more common in both PPMS and SPMS, compared with RRMS (OR 6.1 ( p = 0.002) and 5.7 ( p = 0.003), respectively). The number of lesions per patient involving both the lateral column and extending to GM was independently associated with disability ( p < 0.001). Conclusions: More extensive focal cord lesions, extension of lesions to GM, and diffuse abnormalities are associated with progressive MS and disability.